ROCK PRESSURE DISTRIBUTION IN ZONES OF TECTONIC FAULTS - Rzhevskiy V.V.; Afanasenko G.V.; Davidenko B.Y. (My University, 1988)
Tectonic faults consist of water-saturated rocks crushed and crumbled into gravel and sand fractions, thus facilitating a hydraulic connection between the water-bearing zone and all other rocks till the ground surface. Under these conditions, the rock pressure and the forms of its manifestation depend mainly on the water content of the rocks, the transverse dimensions of the fault zone, and the particle size distribution in the crushed rock in this zone. However, there is no analytical model of mechanical behavior of rock blocks that would take into account the effects of the above factors on the magnitude and the distribution of rock pressure in tectonic fault zones. To solve this problem, physical modeling has been used in which the initial conditions of the experiment can be varied over a wide range. Since the initial stress under which the rock block exists in situ is unknown, worst-case scenario has been assumed in terms of stability of the mine workings. This worst case corresponds to uniaxial (or almost uniaxial) vertical stress field. The horizontal stress being only that produced by lateral thrust.